PLACATING THE DEMONS - Obeyesekere, Gananath. ([S.l.])
1 online resource
Keywords: This book critically examines dominant ceremonial practices in Sri Lanka. It presents key ideas and symbolic systems that exist to this day, in similar shapes or in different guises. It looks at issues such as misfortunes caused by demons (yaksa dosa), an important ceremonial practice known as the puna-ygaya, ideas pertaining to spirit possession, trance, and mediums. It also deals with classical Ayurvedic theories of disease, urban ceremonial practices such as cases of the apotheoses from demon to divinity, as well as multiple forms of Buddhist ceremonial practices that are part of the Sri Lankan consciousness and have found their way into public cultural performances in Sri Lanka. As a comprehensive volume on ceremonial practices in Sri Lanka, this work will be useful for scholars and researchers in cultural studies, sociology, social-anthropology, and particularly those interested in myths and rituals in South Asia.